If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3G + -5 = g + 7 Reorder the terms: -5 + 3G = g + 7 Reorder the terms: -5 + 3G = 7 + g Solving -5 + 3G = 7 + g Solving for variable 'G'. Move all terms containing G to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3G = 7 + 5 + g Combine like terms: -5 + 5 = 0 0 + 3G = 7 + 5 + g 3G = 7 + 5 + g Combine like terms: 7 + 5 = 12 3G = 12 + g Divide each side by '3'. G = 4 + 0.3333333333g Simplifying G = 4 + 0.3333333333g
| 2+0.12m=23.96 | | 80-7.29m=43.55 | | 20.99+76m=214.03 | | 2+12c=20.24 | | 8y-5(6y+11)=121 | | 18.99+0.83x=142.66 | | (y+8)=-2(x-17) | | 300=r(6) | | 8q+17=26 | | u^2-3u+72=0 | | M=S-NforS | | 17X-2X+X=128 | | 153=13S+10 | | 68=10X-2 | | 5000+x/150=y | | g+10=g-10 | | 121x^2-49= | | 0.02y-1.5=8 | | 7f-18=45 | | y/5=9 | | -4.42x+.9=-9.070-.432 | | 0.2(0.1x+0.7)=-0.8 | | 4.5-3.6=3.5+4.8 | | 8i-9=15 | | 7=(w/3)-9 | | 8x-y=3 | | 7=w/3-9 | | (2w+9)(5w-1)=0 | | -(-1.5x-1.5)+8(-1.5)+5=x | | 6b+8=44 | | 3/8=x/16 | | 4=B+1 |